Kaji Eksperimental Turbin Angin Darrieus-H Dengan Bilah Tipe Naca 2415 - Giri Saputra; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The wind turbine is divided into two types: vertical axis wind turbine and horizontal axis wind turbine. A vertical axis wind turbine is likely better than horizontal axis due to unaffected by the direction of the wind and capable for rotating at low wind speeds. The Darrieus-type H is one of vertical wind turbines type, with rotor structure of H-shaped, which capable for a low speed of wind flow areas. Sequence, it meets the Riau Province areas to apply one. This research aim is to test the performance of implementation of a vertical axis wind turbine model, Darrieus type-H blades with naca 2415 in Riau Province area. This research used an experimental method to investigate the vertical axis wind turbine models, Darrieus type-H blades with naca 2415. The wind speeds were chosen on 3.87 m/s, 4.53 m/s, 5.06 m/s, which used a fan as the wind source. Then, the wind of fan was flowed through a simple wind tunnel. The pitch angel was set on 10°, 15°, 20°, 25°, 30°, 80° and 90°, with a load of 250 grams. The results were obtained the optimum performance on a pitch angel of 90°, at wind speed of 3.87 m/s for power generated 0.27 Watts, and the efficiency of 3.81%.Keyword: Pitch angel, Darrieus-H, coefficient of performance